Wisata Berbasis Masyarakat dalam Meningkatkan Kebersihan dan Perekonomian Masyarakat di Desa Pengastulan - Bali - Nasirudin Al Ahsani; Alvion Eky Thorieq (Fakultas Dakwah IAIN Jember, 2020)
Pengastulan Beach is a coast located in the north of the island of Gods, precisely in the Kauman Hamlet, Pengastulan Village, Seririt subdistrict, Buleleng Regency, Bali. In the past, this beach was the same as most beaches in general which were only used as a place to make a living for fishermen. But over time, due to the lack of garbage disposal facilities in Pengastulan Village and many factories dumping their waste to Pengastulan beach, the beach becomes sullied and neglected. The current research uses qualitative research methods. The data was collected through interviews, observation, and documentation. The purpose of this study are to determine the components and facilities of coastal tourism in Pengastulan, to determine community empowerment on the coast of Pengastulan, and to determine the supporting and inhibiting factors of the community empowerment Pengastulan coast. The results of this study show that: 1) The components of Pengastulan beach as a tourist attraction are parking lots, food stalls, boat rentals, cafes, mosques, restrooms, rest areas and many others. 2) Community empowerment is carried out by giving the community full rights to manage their souvenir shops, boat rentals and even to become tour guides. 3) The internal supporting factor comes from the availability of natural resources, such as beach panoramas with sunsets, black sand beaches with sea waves, rich underwater life, and the friendliness of the people. As for the external supporting factors, there are economic growth, increased interest in traveling, cultural diversity and advances in information and technology. The inhibiting factors are resource and preference barriers.